Reducing Vulnerability and Increasing Opportunity : Social protection in the Middle East and North Africa - World Bank. (Washington, DC : World Bank, 2002)
This report provides a framework for a more integrated approach to social protection in the Middle East and North Africa region. It proposes a strategy to guide the reform of social protection system region.
Includes bibliographical references (p. 159-170).
rpm 08/09/2016
Loans
Keywords: Social security; Middle East; Africa, North